2017
DOI: 10.1080/09513590.2017.1411473
|View full text |Cite
|
Sign up to set email alerts
|

The impact of luteinizing hormone supplementation in gonadotropin-releasing hormone antagonist cycles: a retrospective cohort study

Abstract: The impact of exogenous luteinizing hormone (LH) supplementation to patients undergoing controlled ovarian stimulation with gonadotropin-releasing hormone (GnRH) antagonists on cycle outcomes is controversial. Here, we present a retrospective cohort study including cycles from December 2015 to December 2016. Totally 320 cycles were divided into two groups according to with or without exogenous LH supplementation. No significant differences regarding the number of retrieved oocytes, the number of good-quality e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Furthermore, the present study showed that the live birth rate in the fresh cycles was elevated in the study group, which was in accordance with previous studies showing that a higher live birth rate was achieved when r-LH was supplemented in the GnRH antagonist protocol [4][5][6][7]. Exposure to low endogenous LH by downregulation leads to stagnation of endometrial growth [28], decreasing endometrium receptivity [2], and decreasing the implantation rate [28].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the present study showed that the live birth rate in the fresh cycles was elevated in the study group, which was in accordance with previous studies showing that a higher live birth rate was achieved when r-LH was supplemented in the GnRH antagonist protocol [4][5][6][7]. Exposure to low endogenous LH by downregulation leads to stagnation of endometrial growth [28], decreasing endometrium receptivity [2], and decreasing the implantation rate [28].…”
Section: Discussionsupporting
confidence: 92%
“…When comparing the 2 nd ICSI cycles stimulated by r-FSH and r-LH in the GnRH antagonist protocol with the 1 st cycles stimulated with r-FSH for 228 cycles, the implantation rate was increased by 8% in the 2 nd cycles (1 st cycle: 18.57 ± 0.52 vs. 2 nd cycle: 26.47 ± 0.62, p < 0.001) [ 4 ]. A study involving 320 cycles receiving the GnRH antagonist treatment [ 5 ] revealed that exogenous LH supplementation resulted in more oocytes retrieved (5.60 vs. 3.97, p = 0.04) and good-quality embryos (3.07 vs. 1.93, p = 0.01) for patients over 40 years old compared with the r-FSH alone group. Another study involving 1565 cycles [ 6 ] concluded that r-LH supplementation based on the r-FSH stimulation was associated with increased pregnancy rate (61% vs. 54%, p = 0.006), live birth rate (49% vs. 42%, p = 0.01), fertilization rate (74% vs. 72%, p = 0.04), and implantation rate (41% vs. 37%, p = 0.03).…”
Section: Introductionmentioning
confidence: 99%